Sheikh Muhammad al-Khal's choices in his exegesis (Tafsir al-Khal) - Part One as a model - Mahmoud, Asst. Prof. Dr. Sabah Rasoul (Sulaimani Journal for Humanities, 2023)
The Kurds and their scholars have made a significant contribution to serving Islam in all its aspects, especially the scientific and cognitive aspect. Among the prominent Kurds who have a long history in this service is the scholarly sheikh, social reformer, interpreter judge, and linguist: Sheikh Muhammad Ali Amin Al-Khal. His interpretation (Tafsir al-Khal) was one of the most important works of the Sheikh. He wrote it in the Kurdish language and interpreted eight parts of the Holy Qur’an. It was the first interpretation printed in the Kurdish language. Through it, he wanted to help the Kurdish reader understand the Book of God Almighty, contemplate it, and act upon it. In his interpretation, Al-Khal relied on a number of ancient and modern interpretations and was greatly influenced by the reformist school of thought of Sheikh Muhammad Abduh. Sheikh Muhammad Al-Khal has many choices in his interpretation that are in line with his intellectual reformist doctrine. In this research, we highlight his choices in the first part of his interpretation, which are five choices.
Keywords: Selections; Sheikh Muhammad AlKhal; AlKhal Interpretation; Part One